Hippocampal Ganglioside Composition is Altered by Metformin and Liraglutide Treatment in A High-Fat High-Sugar Diet Rat Model - Marin Kuharić; Vedrana Ivić; Milorad Zjalić; Anita Matić; Ines Drenjančević; Sandor G. Vari; Aleksandar Včev; Marija Heffer (Acta Clinica Croatica, 2023)
Insulin resistance has many deleterious effects on the central nervous system, including the initiation and potentiation of neurodegeneration. While the pathogenesis of Alzheimer’s disease has been extensively researched with many insights into the effects of amyloids and neurofibrillary tangles, the connection between the two pathogenic entities has not yet been fully elucidated. Gangliosides are commonly found in neuronal membranes and myelin, specifically in lipid rafts that have been linked to pathological amyloidogenesis. In this study, 64 Sprague Dawley rats with equal sex distribution were separated into four sex-specific groups, as follows: control group on standard diet; group on high-fat, high-sugar diet (HFHSD); group on HFHSD treated with metformin; and group on HFHSD treated with liraglutide. Free-floating immunohistochemistry of the rat hippocampi was performed to analyze group-specific and sex-specific changes in the composition of the four most common gangliosides found in neuronal membranes and myelin sheaths, GM1, GD1a, GD1b and GT1b. The groups on HFHSD showed glucose tolerance impairment and body weight increase at the end of the experiment, whereas the groups treated with pharmacotherapeutics had better insulin sensitivity and decreases in body weight by the end of the experiment. Most changes were observed for GM1 and GD1b. Positive immunoreactivity for GM1 was observed in the male group treated with liraglutide in regions where it is not physiologically found. The changes observed following HFHSD and liraglutide treatment were suggestive of ganglioside restructuring that might have implications on pathological amyloidogenesis. Metformin treatment did not significantly alter the hippocampal ganglioside composition in either sex.